Being 'indecisive' in Japanese: Analysis of kana, darou ka and (n) janai ka - Asano-Cavanagh, Yuko (John Benjamins Publishing Company, 2016)
Japanese speakers are often characterised as ‘indecisive’. The indecision is indicated by epistemic markers being frequently added to express the doubt. The sentence-final particle kana shows an indecisive attitude and is usually translated into English as I wonder or maybe. There are other similar Japanese expressions, for example, darou ka and (n) janai ka. Both expressions represent uncertainty and are generally interpreted as I wonder or maybe. Although kana, darou ka and (n) janai ka are often treated as ‘synonyms’, they are not necessarily interchangeable. The aim of this study is to define these Japanese epistemic markers using the reductive paraphrase methodology of the Natural Semantic Metalanguage approach. New definitions are presented to clarify semantic differences and the invariant concept embedded in each expression. This analysis elucidates Japanese speakers’ epistemic stance when they are in doubt.